Mobile Pedagogy in Higher Education: A Comprehensive Analysis of Mobile Learning Practices for Classroom Management in Usmanu Danfodiyo University, Sokoto State, Nigeria - Abubakar, Usman (Indonesian Scientific Publication, 2024)
The study investigated the awareness, utilization, and relevance of mobile devices for classroom management at Usmanu Danfodiyo University Sokoto State, Nigeria. A descriptive survey research design was used for the study. The study was guided by three research questions. The population of the study comprises all lecturers of Usmanu Danfodiyo University Sokoto. Multistage sampling technique was used; first stage, simple random sampling was used, second stage, proportionate sampling, third stage, snowball sampling technique was used to select a total sample of 526 respondents (165 lecturers). The instrument used for data collection was the researcher's self-constructed questionnaire titled Lecturers' Perception on the Utilization of Mobile Devices in Teaching (LPUMT) which was validated by experts and pilot-tested, yielding a reliability index of 0.67 through Cronbach Alpha analysis. Frequency counts and percentages were used to analyze the demographic information and answer the research questions. The study's findings revealed that lecturers are aware of and use mobile devices in classroom management. The study has also confirmed the relevance of mobile devices in classroom management at UDUS. The study recommends awareness programs that will enable lecturers to recognize the importance of using mobile technology in the educational system. The study also recommends Viable learning programs and applications accessible using mobile devices for both teachers and students in tertiary institutions should be created. These initiatives, as suggested by the study, are crucial for harnessing the full potential of mobile pedagogy in higher education settings.